Yukon First Nation wildlife harvest data collection and management : lessons learned and future steps - Lavallée, Michel Thomas (2010)
The Yukon Umbrella Final Agreement was signed in 1993 and Chapter 16 allows Yukon First Nations to govern wildlife harvest on traditional territories. First Nation governments manage wildlife using traditional ecological knowledge and have started to collect harvest data to inventory wildlife use and incorporate in management. A workshop, hosted near Lake Laberge by Ta'an Kwäch'än, facilitated discussion amongst First Nation delegates regarding wildlife harvest data collection was conducted November 5 and 6, 2009. A questionnaire was conducted prior to the workshop to provide guidance for discussion topics. The workshop had four objectives: 1) understand the importance of First Nation harvest data and how the data will be used during management decisions, 2) discuss methods used to collect harvest data and potential for a unified approach, 3) discuss potential methods for storing data, protecting confidentiality while allowing effective management, and 4) produce a document that can be used to implement or improve harvest data collection. This project will fulfill the fourth objective by summarizing the workshop content, explore the factors that promote and hinder data collection, and the intermediate and long-term objectives that will allow First Nation governments to become effective co-management partners while ensuring their traditional lifestyle and connection to the land is not lost.